Nitrogen-loss and associated microbial communities in sediments from the Yangtze Estuary and adjacent sea - Teng, Zhenzhen; Zhen, Yu; Yu, Zhigang; Mi, Tiezhu; Cai, Tao (Frontiers in Marine Science, 2022)
Denitrification and anammox play the crucial role for N removal processes in coastal 18 ecosystems, but the ecological distribution of denitrifying and anammox 19 microorganisms and their N removal rates in the Yangtze Estuary and its adjacent sea 20 are required in-depth analysis. Here, we utilized high-throughput sequencing, qPCR, 21 and 15N isotope to reveal the community structure and function of denitrifying and 22 anammox microorganisms in the surface sediments from Yangtze Estuary and 23 adjacent sea. The results suggested that the gene abundances of nirS and nirK for 24 denitrifiers were higher than AMX 16S rRNA for anammox bacteria. The genera 25 composition of nirS- and nirK-encoding denitrifiers communities showed different 26 distribution patterns. Furthermore, Candidatus Anammoximicrobium dominated the 27 anammox community, implying the anammox oxidation capacity of the other genera 28 should be noted in marine sediments. Compared to anammox, denitrification was the 29 dominant contributor of nitrogen removal process and contributed 73.5% on average. 30 The sediment Chla was the key factor to regulate denitrification and anammox rates, 31 indicating the fresh organic matter was more labile and easier to be utilized by NOx− removal processes.